“QUALITY ASSESSMENT OF NUTRITION INFORMATION PUBLISHED WEEKLY IN THE SURROUNDING OF FOUR HOSPITALS IN LIMA, PERU“ - Del Carpio Carhuas, T. (2022)
“There is a growing demand from the general public regarding nutrition topics that has prompted social media such as magazines, newspapers, television, radio and the internet to include more nutritional content. The purpose of this study was to assess the quality of nutrition information published by health weeklies in the surroundings of four hospitals in Lima, Peru. A cross- sectional study was conducted using a mixed methodological design involving both quantitative and qualitative analyses. Thirtyseven hard copies of 4 health weeklies were purchased over the 10- week study period. Bivariate Logistic Regression was performed to examine all available journal characteristics associated with the quality of provided information. Logistic Regression Models were estimated for the independent variables that showed statistical significance in the bivariate analysis. Weekly publications with the highest percentage of pages dedicated to nutrition were “My Health” (41.67%), “Natural Health” (48.6%) and those with the lowest percentage were “Sun, medicine and beauty” (19.37%) and “Health, Money and Love” (18.34%). Collected publications included 185 articles that were classified into two groups regarding the validity of the nutrition information presented: supported 50.3% (93/185) and unsupported 49.7% (92/185). Statistical analysis for quality estimated that the “name of weekly” had a p value=0.000, the “topic” had a p value=0.035, and the “objective, source description, quarter of publications” had a p value >0.05. Multivariate logistic regression reports that only the variable “name of the weekly” had statistical significance with p values less than 0.05. The percentage of nutrition information suggests that editors may not be applying journalistic principles and shows the importance of interdisciplinary work, between nutritionists and health journalists, to improve health status of the general population. In the case of weekly health publications, editors responsible for this type of written press could benefit from including nutritionists in charge of providing nutritional information. “